Multiple Regulatory Modules Are Required for Scale-to-Feather Conversion. (21st November 2017) - Wu, Ping; Yan, Jie; Lai, Yung-Chih; Ng, Chen Siang; Li, Ang; Jiang, Xueyuan; Elsey, Ruth M; Widelitz, Randall; Bajpai, Ruchi; Li, Wen-Hsiung; Chuong, Cheng-Ming
Abstract: The origin of feathers is an important question in Evo-Devo studies, with the eventual evolution of vaned feathers which are aerodynamic, allowing feathered dinosaurs and early birds to fly and venture into new ecological niches. Studying how feathers and scales are developmentally specified provides insight into how a new organ may evolve. We identified feather-associated genes using genomic analyses. The candidate genes were tested by expressing them in chicken and alligator scale forming regions. Ectopic expression of these genes induced intermediate morphotypes between scales and feathers which revealed several major morphogenetic events along this path: Localized growth zone formation, follicle invagination, epithelial branching, feather keratin differentiation, and dermal papilla formation. In addition to molecules known to induce feathers on scales (retinoic acid, β-catenin ), we identified novel scale-feather converters ( Sox2, Zic1, Grem1, Spry2, Sox18 ) which induce one or more regulatory modules guiding these morphogenetic events. Some morphotypes resemble filamentous appendages found in feathered dinosaur fossils, whereas others exhibit characteristics of modern avian feathers. We propose these morpho-regulatory modules were used to diversify archosaur scales and to initiate feather evolution. The regulatory combination and hierarchical integration may have led to the formation of extant feather forms. Our study highlights the importance of integrating discoveries between developmental biology and paleontology.